A collision-dominated regime in electrodynamic particulate suspension. (June 2022) - Ling, H.; Higuera, F.J.
Abstract: Electrodynamic particulate suspension is a technique to generate suspensions of electrically conducting particles by overcoming their weight with the electric force that acts on the particles when they are enclosed in the gap between two horizontal electrodes to which a high voltage is applied. The particles move then up and down in the gap, colliding with the electrodes and with other particles. A collision-dominated regime is analyzed in which the time between interparticle collisions is short compared with the time it takes for a particle to cross the gap. Conservation equations for the number and charge densities of particles in the gap are derived neglecting the inertia of the particles. These equations are coupled with a Poisson equation for the electric potential and with mass and momentum conservation equations for the gas in the gap, which is set in motion by the drag of the particles. In agreement with experimental results (Shoshin and Dreizin, 2002), solutions of this problem display a transition between stationary suspensions and non-stationary suspensions characterized by the continuous generation of electrohydrodynamic plumes at the lower electrode. The transition occurs when the number of suspended particles per unit electrode area in the stationary state becomes larger than a certain value. Highlights: A collision-dominated regime for electrodynamic particulate suspension (EPS) is analyzed. Conservation equations for the number and charge densities of suspended particles are derived. These equations are coupled with a Poisson equation for the electric potential and mass and momentum equations for the gas. Solutions of these equations are computed and discussed.